Pemberdayaan Membangun Kesadaran Sholat Berjamah di Masjid Al-Ihsan Dusun Krajan Desa Karangpatihan Kecamatan Pulung Kabupaten Ponorogo - Samsul Hadi; Ibnu Muchlis (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research is motivated by the fact that some people lack understanding and awareness and are lazy to come to the mosque to carry out congregational prayers and the strong influence of the environment, busy work activities. The formulation of the problem in this study is how to carry out congregational prayers in Karang Patihan Pulung Ponorogo Village, East Java and what problems are encountered in holding congregational prayers in Karang Patihan Pulung Ponorogo Village, East Java. This research was conducted using the ABCD (Asset Based Community Development) method with a qualitative approach that is descriptive analysis, with data collection techniques through observation, interviews, and studies that influence the community not to pray in congregation seen from internal factors. Documentation, the subjects in this study were determined by using purposive sampling technique. The results of this study indicate that in general it is revealed that, the understanding of the people of Dusun Krajan towards congregational prayers at the mosque is a lack of awareness that affects the community not to pray in congregation seen from internal factors. In general, that is, most people rarely pray in congregation at the mosque, people feel lazy to pray in congregation, because some people think that praying in congregation is long, and people prefer to do work activities rather than praying in congregation. Meanwhile, specifically it was revealed that the community felt they did not understand themselves in carrying out congregational prayers at the mosque, lack of religious knowledge from the neighborhood and lack of religious knowledge from the neighborhood and lack of interest in the community refusing invitations from the neighborhood community not to perform congregational prayers in congregational prayers regularly every day.